A Diagnostic Test on Grammatical Structures for English Teachers - Tyas, Agnes Siwi Purwaning (Magister Kajian Bahasa Inggris (English Language Studies) Universitas Sanata Dharma Yogy, 2015)
Grammar is a significant part of English proficiency. English proficiency also coverscommunicative linguistic aspects that require the speakers to comprehend and use thelinguistic aspects of language, as well as their functions and rules (Common EuropeanFramework of Reference for languages, 1971). Considering the importance of grammaraccuracy in English proficiency, teachers need to master the language forms, the functionsand the contexts of use before they can share their knowledge to their students. In order tomeasure teachers‘ proficiency on grammatical structures, this research is conducted to designa diagnostic test. A needs analysis questionnaire was distributed to 24 English teachers toidentify the grammatical structures that they need to review and the urgency. The result of thequestionnaire was used to determine the number of test items for each structure. The resultsof the diagnostic test were used to design a review program to help teachers review andimprove their competence on grammatical structures based on their needs. Keywords: grammar, diagnostic test, proficiency